Buku Ilustrasi Banten Prayascita Gaya Flat Design Sebagai Sarana Pelestarian Budaya Bali Pada Parisada Hindu Dharma Indonesia Bekasi - Cista, Luh Putu Ayu Cista; Murtono, Taufik (ISI Press Institut Seni Indonesia Surakarta, 2023)
This Illustrated Book as a Means of Preserving Balinese Culture was designed after seeing traditions and culture that are slowly being abandoned by the Balinese Hindu community, especially teenagers who are outside the island of Bali. Data collection through observation and interviews with sources from Hindu religious leaders in Bekasi who know about Banten Prayascita. The visual design process for illustration books using the Design Thinking and Style methods in flat design illustrations is taken for its modern, minimalist nature. The illustrations in the book refer to the original form of Banten, Serati Banten as a reference for supporting illustrations, and the color palette is taken from one of the components in Banten such as flowers, leaves, incense and coconut leaves, supergraphics designed from Banten components such as shrimp paste, thread, and so on. The design of promotional media using the work method uses the AISAS method. By designing this Illustrated Book, it is hoped that the Banten Prayascita tradition will be reintroduced to the young Balinese Hindu community and help preserve and inherit the Banten Prayascita tradition.